What impact does teaching a structured set of literacy lessons based around ‘Transactional Strategies Instruction’ for reading comprehension have on a class of mixed-ability Year 6 students, learning in a second language? - McCann, Helen (2017)
This project researched the teaching of reading comprehension to Year 6 students who were underachieving in standardized tests. With the aim of improving levels of comprehension and attitudes towards reading, an action research model was adopted, using questionnaires, Statutory Assessment Tests, and a reflective journal. The four-week research period involved teaching a structured set of literacy lessons based on Transactional Strategies Instruction. The findings demonstrated a positive increase in standardized test results as well as a significant change in the student’s attitudes towards an appreciation of reading. The findings have illustrated the need for a complete review of the teaching of reading comprehension within the Key Stage 2 department at my school. The project raised additional questions about the implications of gender, culture, and languages, all of which are areas for possible further research.